Department of Chemical Engineering - (:unkn) unknown (My University, 2026)
Both the environment and science/technology have attracted attention in recent years as themes addressing major needs of the industry and the society as a whole. The goal of the undergraduate programme of the Department of Environmental Science and Technology is to educate students in a combination of life and environmental sciences and technology to meet the worlwide needs in this area. The main feature of the program, which is unique in Cyprus, is its educational structure in which the Department's faculty work together to teach a variety of topics in the field of Environmental Science and Technology. After complementing lectures with practical education, students are assigned to laboratories in diverse fields during their senior year while undertaking research for their degree.